Pendidikan Islam Inklusif-Multikultural dalam Perspektif Teori Gestalt - Mohamad Yasin Yusuf (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
Islamic education is mostly dominated by the inherited construction of classical-scholastic epistemology where there is less appreciation of the dynamics and development of life which are increasingly complex and diverse. Many religious groups have the ideology leading to the truth which is excessive, unilateral, and exclusive. This is the reason why it is important to develop a paradigm of inclusive-multicultural education, the process of developing the full potential of human beings who appreciate plurality and heterogeneity as a consequence of the diversity of cultural, ethnic, tribal and flow (religion). At this point, Gestalt theory can be used as a surgical glasses in viewing the problem. According to Gestalt theory, diversity is a part / piece of totality that must be construed as a whole, not simply interpreted in bits and pieces. Overall, it would be more meaningful than just a piece or pieces that are not obscure. Therefore, understanding pluralistic inclusive life will give understanding of exclusion in Islamic education.